Phloem Loading Strategies and Water Relations in Trees and Herbaceous Plants(1)([W])([OA]) - Fu, Qiushi (American Society of Plant Biologists, 2011)
Most herbaceous plants employ thermodynamically active mechanisms of phloem loading, whereas in many trees, the mechanism is passive, by diffusion. Considering the different water transport characteristics of herbs and trees, we hypothesized that water relations play a role in the adoption of phloem loading strategies. We measured whole-plant hydraulic conductance (K(p)), osmolality, concentrations of polar metabolites, and key inorganic ions in recently mature leaves of 45 dicotyledonous species at midafternoon. Trees, and the few herbs that load passively, have low K(p), high osmolality, and high concentrations of transport sugars and total polar metabolites. In contrast, herbs that actively load sucrose alone have high K(p), low osmolality, and low concentrations of sugars and total polar metabolites. Solute levels are higher in sugar alcohol-transporting species, both herbs and trees, allowing them to operate at lower leaf water potentials. Polar metabolites are largely responsible for leaf osmolality above a baseline level (approximately 300 mm) contributed by ions. The results suggest that trees must offset low K(p) with high concentrations of foliar transport sugars, providing the motivating force for sugar diffusion and rendering active phloem loading unnecessary. In contrast, the high K(p) of most herbaceous plants allows them to lower sugar concentrations in leaves. This reduces inventory costs and significantly increases growth potential but necessitates active phloem loading. Viewed from this perspective, the elevation of hydraulic conductance marks a major milestone in the evolution of the herbaceous habit, not only by facilitating water transport but also by maximizing carbon use efficiency and growth.